Characteristics od transport modals and requirements to logistics simulations - Ornellas, Alander; Campos, Renato de (Revista Gestão da Produção Operações e Sistemas, 2008)
There are many requirements to enterprise games design, which are employed on learning at various levels. For example, to design an enterprise game in the logistic area, it is necessary the adaptation of the game parameters related to transport modals according to the reality of each country or region. Others characteristics of the games are related to the support technology. This paper presents a study about transport modals, emphasizing its importance to cost management and service level of a logistic system and, consequently, to enterprise games. This work presents a literature revision about transport modals. This study intends to support decisions making in enterprises logistic systems and to define characteristics of a conceptual model to develop a logistic enterprise game. Then, the enterprise game LOGIN is presented followed by a comparison with others enterprise games found in the academic area. The criterias analyses are: Strategic Areas, Elements of the Supply Chain, Resources of Execution and Presentation, and Flexibility Level. The main objective is to supply information about requirements to design or to apply enterprise games to the logistic area. Key-words: Logistic, Transport, Enterprise games, Learning.